Utilisation of TikTok as a Medium for Education, Publication, and Promotion in Sarirejo Village: Pemanfaatan Media Tiktok Sebagai Sarana Edukasi, Publikasi, dan Promosi di Desa Sarirejo - Yusnia I’anatur Rofiqoh; Ananda Zulfa Atiqoh; Bagas Aditya Pratama; Miftakhus Syifa; Daghastani F. A (Academia Open, 2024)
TikTok has experienced rapid growth as a short-form video social media platform that is not only used for entertainment but also has great potential as a means of education, publication, and promotion. This study aims to explore the use of TikTok by the community of Sarirejo Village in educating the public, disseminating village information, and promoting local products and culture. The research approach used is qualitative with a descriptive method. Data was collected through observation of TikTok content created by village residents, in-depth interviews with local creators and village officials, and documentary studies. The results indicate that TikTok significantly enhances community engagement in information dissemination and digital marketing. Educational content presented visually and attractively is proven to be more easily accepted by various segments of society. Additionally, the publication of village activities through TikTok creates transparency and encourages citizen participation. Meanwhile, the promotion of local products through TikTok has increased the market appeal of village products to external markets. Despite challenges such as limited digital literacy and internet access, the potential of TikTok as a village communication tool is immense. Continuous training and support from the village government are necessary to optimise the use of TikTok in supporting village development. Highlights: Effective Communication – TikTok boosts public education and information sharing. Economic Impact – Promotes local products, expanding market reach. Digital Challenges – Requires training to overcome literacy and access gaps. Keywords: TikTok, Digital Education, Village Publications, Local Promotion, Social Media